A comparative study of software programmes for cross‐sectional skeletal muscle and adipose tissue measurements on abdominal computed tomography scans of rectal cancer patients. Issue 2 (22nd November 2016) - van Vugt, Jeroen L.A.; Levolger, Stef; Gharbharan, Arvind; Koek, Marcel; Niessen, Wiro J.; Burger, Jacobus W.A.; Willemsen, Sten P.; de Bruin, Ron W.F.; IJzermans, Jan N.M.
Abstract: Background: The association between body composition (e.g. sarcopenia or visceral obesity) and treatment outcomes, such as survival, using single‐slice computed tomography (CT)‐based measurements has recently been studied in various patient groups. These studies have been conducted with different software programmes, each with their specific characteristics, of which the inter‐observer, intra‐observer, and inter‐software correlation are unknown. Therefore, a comparative study was performed. Methods: Fifty abdominal CT scans were randomly selected from 50 different patients and independently assessed by two observers. Cross‐sectional muscle area (CSMA, i.e. rectus abdominis, oblique and transverse abdominal muscles, paraspinal muscles, and the psoas muscle), visceral adipose tissue area (VAT), and subcutaneous adipose tissue area (SAT) were segmented by using standard Hounsfield unit ranges and computed for regions of interest. The inter‐software, intra‐observer, and inter‐observer agreement for CSMA, VAT, and SAT measurements using FatSeg, OsiriX, ImageJ, and sliceOmatic were calculated using intra‐class correlation coefficients (ICCs) and Bland–Altman analyses. Cohen's κ was calculated for the agreement of sarcopenia and visceral obesity assessment. The Jaccard similarity coefficient was used to compare the similarity and diversity of measurements. Results: Bland–Altman analyses and ICC indicated that the CSMA, VAT, and SAT measurements between the different software programmes were highly comparable (ICC 0.979–1.000, P < 0.001). All programmes adequately distinguished between the presence or absence of sarcopenia (κ = 0.88–0.96 for one observer and all κ = 1.00 for all comparisons of the other observer) and visceral obesity (all κ = 1.00). Furthermore, excellent intra‐observer (ICC 0.999–1.000, P < 0.001) and inter‐observer (ICC 0.998–0.999, P < 0.001) agreement for all software programmes were found. Accordingly, excellent Jaccard similarity coefficients were found for all comparisons (mean ≥ 0.964). Conclusions: FatSeg, OsiriX, ImageJ, and sliceOmatic showed an excellent agreement for CSMA, VAT, and SAT measurements on abdominal CT scans. Furthermore, excellent inter‐observer and intra‐observer agreement were achieved. Therefore, results of studies using these different software programmes can reliably be compared.